Peningkatan Hasil Belajar Matematika Murid Melalui Gamifikasi Multi-platform pada Model Discovery Learning - Indah Febbry Anitasari; Lady Agustina; Ika Aldrina Juliastuti (Universitas Islam Jember, 2026)
This study aimed to enhance students' mathematics learning outcomes on vector topics through the integration of multi-platform gamification into the Discovery Learning model. Following the Kemmis and McTaggart framework, this classroom action research was conducted over two cycles involving 35 students from class XI-7 at SMAN Pakusari in the 2025/2026 academic year. Quizizz served as the exit ticket-based formative assessment in Cycle I, while Kahoot was employed in Cycle II. Data were gathered through observations and tests. The results showed that the average score rose from 58.43 in the pre-cycle to 79.11 in Cycle I, and further to 89.51 in Cycle II. Mastery learning rates increased from 22.86% to 62.86%, and ultimately reached 94.29%. Student activity improved from 64% to 86%, while teacher activity increased from 71% to 92%. Thus, the integration of multi-platform gamification into Discovery Learning proved effective in improving students' mathematics learning outcomes. Keywords: Mathematics Learning Outcomes, Multi-platform Gamification, Discovery Learning